Peluang dan Tantangan Bisnis di Era Digital Menurut Perspektif Islam (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Digital technology has, in many ways, altered the manner in which businesses function. This transformation touches on aspects like how products are developed, delivered, and sold. It opens up a range of possibilities for business owners to broaden their markets, boost profits, and make better use of online tools. At the same time, however, the digital age introduces certain difficulties. These include increased competition as well as risks related to practices that may conflict with sharia law—for example, charging interest, engaging in transactions with unclear risks, or producing counterfeit goods. The focus of this study is to examine the opportunities and challenges that businesses encounter in today’s digital world, viewed through an Islamic lens. The approach taken involves a review of existing literature, drawing from various sources dealing with digital commerce and Islamic economic principles. The results suggest that digital business ventures hold considerable promise, provided they are conducted with honesty, fairness, and transparency, while avoiding activities disallowed by sharia. This way, entrepreneurs can not only generate income but also develop their enterprises in a way that aligns with ethical and religious values.